Reactivity of cuin4flattened Complexes: Interplay Between Coordination Geometry and Ligand Flexibility - Lemus-Chavez, L; Lemus-Chavez, L; Vera-Oyarce, C; Vera-Oyarce, C; Aravena-Ponce, D; Aravena-Ponce, D; Llanos-Silva, L; Llanos-Silva, L (American Chemical Society, 2020)
The relation between redox activity and coordination geometry in CuIN4 complexes indicates that more flattened structures tend to be more reactive. Such a preorganization of the ligand confers to the complex geometries closer to a transition state, which has been termed the "entatic"state in metalloproteins, more recently extending this concept for copper complexes. However, many aspects of the redox chemistry of CuI complexes cannot be explained only by flattening. For instance, the role of ligand flexibility in this context is an open debate nowadays. To analyze this point, we studied oxidation properties of a series of five monometallic CuI Schiff-base complexes, [CuI(Ln)]+, which span a range of geometries from a distorted square planar (n = 3) to a distorted tetrahedron (n = 6, 7). This stepped control of the structure around the CuI atom allows us to explore the effect of the flattening distortion on both the electronic and redox properties through the series. Experimental studies were complemented by a theoretical analysis based on density functional theory calculations. As expected, oxidation was favored in the flattened structures, spanning a broad potential window of 370 mV for the complete series. This orderly behavior was tested in the reductive dehalogenation reaction of tetrachloroethane (TCE). Kinetic studies show that CuI oxidation by TCE is faster as the flattening distortion is higher and the oxidation potentials of the metal are lower. However, the most reactive complex was not the more planar, contradicting the trend expected from oxidation potentials. The origin of this irregularity is related to ligand flexibility and its connection with the atom/electron transfer reaction path, highlighting the need to consider effects beyond flattening distortion to better understand the reactivity of this important class of complexes. ©